2023
DOI: 10.1039/d3qi00678f
|View full text |Cite
|
Sign up to set email alerts
|

N-heterocyclic carbene-ligated metal complexes and clusters for photocatalytic CO2reduction

Abstract: Photocatalytic reduction of CO2 to high valued-added production is a green and sustainable approach to reducing excessive CO2 emissions. N-heterocyclic carbenes (NHCs) are an emerging class of versatile ligands due...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…[16][17]41,[44][45][46][47] Furthermore, the new Ag(I)-NHC complexes have been employed in a range of catalytic reactions, such as cross-coupling reactions, CÀ H activation, and asymmetric transformations. [48][49] Recently, there has been a significant development in the design and utilization of silver complexes. These complexes contain bulky and electron-rich donor-functionalized NHC ligands, which have shown promising potential as antimicrobial and antitumor agents.…”
Section: Introductionmentioning
confidence: 99%
“…[16][17]41,[44][45][46][47] Furthermore, the new Ag(I)-NHC complexes have been employed in a range of catalytic reactions, such as cross-coupling reactions, CÀ H activation, and asymmetric transformations. [48][49] Recently, there has been a significant development in the design and utilization of silver complexes. These complexes contain bulky and electron-rich donor-functionalized NHC ligands, which have shown promising potential as antimicrobial and antitumor agents.…”
Section: Introductionmentioning
confidence: 99%
“…13–15 On the other hand, as one of the more widely studied MOFs, UiO-68-type MOF photocatalysts have been extensively prepared for photocatalytic organic transformation. 16–20 However, the limited tunability hampers their deeper exploration. In view of the tunable absorption properties of benzothiadiazoles, we envision replacing the central benzene ring of the [1,1′:4′,1-terphenyl]-4,4′′-dicarboxylic acid (TPDC) linker with 2,1,3-benzothiadiazole units to systematically modulate the absorption properties and charge-transfer kinetics of UiO-68-type MOFs while maintaining the topological structure of the synthetic MOFs (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Molecular corks can also affect the structure and reactivity of catalytic metal surfaces. ,,, Recently, the use of CO on Pd/Au(111) SAAs to modify the active sites of SAA catalysts has been demonstrated via density function theory (DFT) calculations and then confirmed via experiment . DFT studies have shown the ability of CO to influence the morphology of 15 distinct SAAs .…”
Section: Introductionmentioning
confidence: 99%